Yearly Energy, Exergy, and Environmental (3E) Analyses of A Photovoltaic Thermal Module and Solar Thermal Collector in Series - AL-aridhee, Sameer Teref Azeez; Moghiman, Mohammad (Al-Khwarizmi Engineering Journal, 2023)
The annual performance of a hybrid system of a flat plate photovoltaic thermal system and a solar thermal collector (PVT/ST) is numerically analyzed from the energy, exergy, and environmental (CO2 reduction) viewpoints. This system can produce electricity and thermal power simultaneously, with higher thermal power and exergy compared to conventional photovoltaic thermal systems. For this purpose, a 3D transient numerical model is developed for investigating the system’s performance in four main steps: (1) investigating the effects of the mass flow rate of the working fluid (20 to 50 kg/h) on the temperature behavior and thermodynamic performance of the system, (2) studying the impacts of using glass covers on the different parts of the system, (3) evaluating the annual energy and exergy analyses of the system under Mashhad weather conditions, and (4) examining the CO2 reduction by using the proposed system. The results show that for the (glazed) PVT and (glazed) ST systems, increasing the mass flow rate of the working fluid from 20 to 50 kg/h results in 22% and 1.5% improvements in both thermal and electrical power, respectively. However, the thermal exergy of the system decreases by 40.1%. Furthermore, the (glazed) PVT/(glazed) ST systems generate approximately 86% and 264% more thermal power and energy than the PVT/ST systems, respectively. Using a (glazed) PVT/(glazed) ST system with a working fluid’s mass flow rate of 50 kg/h results in maximum thermal and electrical efficiencies of 40.7% and 16.22%, respectively. According to the annual analysis, the highest average thermal and electrical power, equal to approximately 338.3 and 24 W, respectively, is produced in August. The amount of CO2 reduction increases by increasing the mass flow rate and using a glass cover. The PVT/(glazed)ST system has the potential to reduce CO2 emissions by 426.3 kg per year.